The Quasar Feedback Survey: revealing the interplay of jets, winds, and emission-line gas in type 2 quasars with radio polarization. Issue 3 (15th April 2022) - Silpa, S; Kharb, P; Harrison, C M; Girdhar, A; Mukherjee, D; Mainieri, V; Jarvis, M E
ABSTRACT: We present results from a combined radio polarization and emission-line study of five type 2 quasars at z < 0.2 with the Karl G. Jansky Very Large Array (VLA) B-array at 5 GHz and Hubble Space Telescope ( HST ) [O iii ] observations. These five sources are known to exhibit close association between radio structures and ionized gas morphology and kinematics. Four sources (J0945+1737, J1000+1242, J1356+1026, and J1430+1339) show polarization in the current data. J1010+1413 is the unpolarized source in our sample. We detect $0.5{-}1{{\ \rm per\ cent}}$ fractional polarization in the radio cores and a high fractional polarization ($10{-}30{{\ \rm per\ cent}}$ ) in the lobes of these sources. The morphological, spectral, and polarization properties suggest a jet origin for radio emission in J0945+1737, J1000+1242, J1010+1413, and J1430+1339 whereas the current data cannot fully discern the origin of radio emission (jet or wind) in J1356+1026. An anticorrelation between various polarized knots in the radio and [O iii ] emission is observed in our sources, similar to that observed in some radio-loud AGN in the literature. This suggests that the radio emission is likely to be depolarized by the emission-line gas. By modelling the depolarization effects, we estimate the size of the emission-line gas clouds to be ∼(2.8 ± 1.7) × 10 −5 parsec and the amount of thermal material mixed with the synchrotron plasma to be ∼(1.01 ± 0.08) × 10 6  M⊙ in the lobe of J0945+1737 (which exhibits the most prominent polarization signature in its lobe). The current work demonstrates that the interplay of jets/winds and emission-line gas is most likely responsible for the nature of radio outflows in radio-quiet AGN.